Are there task-specific effects in morphological processing? Examining semantic transparency effects in semantic categorisation and lexical decision. Issue 11 (November 2022) - Chee, Qian Wen; Yap, Melvin J
Current theories of morphological processing include form-then-meaning accounts, form-with-meaning accounts, and connectionist theories. Form-then meaning accounts argue that the morphological decomposition of complex words is based purely on orthographic structure, while form-with meaning accounts argue that decomposition is influenced by the semantic properties of the stem. Connectionist theories, however, argue that morphemes are encoded as statistical patterns of occurrences between form and meaning. The weight of evidence from the literature thus far suggests that morphological decomposition is best explained by form-then-meaning accounts. That said, conflicting empirical findings exist, and more importantly, semantic transparency effects in morphological processing have been examined almost exclusively with the lexical decision task, in which participants discriminate between words and nonwords. Consequently, the extent to which observed results reflect the specific demands of the lexical decision task remains unclear. The present study extends previous work by testing whether the processing dynamics of early morphological processing are moderated by task requirements. Using the masked morphological priming paradigm, this hypothesis was tested by examining semantic transparency effects for a common set of words across semantic categorisation and lexical decision. In both tasks, priming was stronger for transparent (e.g., painter-PAINT) than opaque (e.g., corner-CORN) prime–target pairs; these results speak against form-then-meaning accounts. These findings further inform theories of morphological processing and underscore the importance of examining the interplay between task-general and task-specific mechanisms.